Mechanical properties of fly ash geopolymer mortar reinforced with polypropylene fibers (Journal of University of Babylon for Engineering Sciences, 2017)
Geopolymers are new ceramic substances with the possibility to supplant Portland concrete in a wide scope of uses, from immobilization of substantial metals to concerts for structural designing. They rely on the alkaline activation of aluminosilicates, for example, blast furnace slag, pulverized fly ash, and metakaolin. Notwithstanding their high mechanical strength what's more, chemical durability, geopolymer concretes are in as a rule set apart with high permeability and porosity, which could contrarily influence the long-term durability or performance of concretes. This paper utilizes polypropylene fibers to enhance the geopolymer mechanical properties. Four percentage of polypropylene fibers where utilized which were 0.2, 0.5, 1 and 1.5% by weight of fly ash. The impact of these percentage on flow, dry density, mechanical strength, in expansion to flexural strength, were resolved. Results have demonstrated that the addition of polypropylene fibers lead very slightly decreased in the dry density, and decreased the flow, while it lead to enhance the flexural and compressive strength. The best percentage that give higher compressive and flexural strength was the one with a 0.5% addition by weight of fly ash.